2007
DOI: 10.3104/reports.2022
|View full text |Cite
|
Sign up to set email alerts
|

Oral health condition and treatment needs of a group of Nigerian individuals with Down syndrome

Abstract: Individuals with Down syndrome in Nigeria have poorer oral health and more treatment needs than controls. They would benefit from frequent oral health assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
112
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(124 citation statements)
references
References 19 publications
(22 reference statements)
9
112
3
Order By: Relevance
“…From the ethical perspective, dentists must accept the responsibility and commitment to contribute with their knowledge to improve the quality of life of these people [9]. Though children with DS can be excellent orthodontic patients, orthodontic prognosis may be poor because of their learning disability, parafunctional habits and severe periodontal disease [17]. This investigation reinforces the need for further studies on this issue, including studies of the functional and psychosocial impacts of malocclusions in DS patients.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…From the ethical perspective, dentists must accept the responsibility and commitment to contribute with their knowledge to improve the quality of life of these people [9]. Though children with DS can be excellent orthodontic patients, orthodontic prognosis may be poor because of their learning disability, parafunctional habits and severe periodontal disease [17]. This investigation reinforces the need for further studies on this issue, including studies of the functional and psychosocial impacts of malocclusions in DS patients.…”
Section: Discussionmentioning
confidence: 61%
“…Oredugba [17] found 51% of class I and 47% of class III among 43 individuals with DS and only 5% of class III in the control group (P<.05). In this study most of the cases were class I in both groups.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…[ there is no difference in risk compared with the general population. Some reports concluded that DS population are with higher caries prevalence, [27,28] while others concluded that there is no difference in caries prevalence compared to healthy groups. [29][30][31][32][33] However, most investigators have found a lower prevalence of caries in DS patients in both dentitions.…”
Section: Sexual Developmentmentioning
confidence: 99%
“…Autosomal chromosome abnormalities in Down syndrome as known as trisomy 21, causes oral manifestations consist of hypoplasia, delayed tooth eruption 2-3 years longer, persistence of primary teeth, hypodontia, skeletal abnormalities which cause class III occlusion relationship and openbite (Cheng et al, 2011;De Moraes et al, 2007;Oredugba, 2007;Areias et al, 2011).…”
Section: Introductionmentioning
confidence: 99%